Tuberculosis Screening in Patients with Diabetes Mellitus at the Internal Medicine Clinic of UGM Academic Hospital: Descriptive Study - Hariyanto, Suci Wahyu; Avidati, Herfis; Ulfah, Undatun; Nurlaily, Arinda Nia; Tejaningrum, Krista Dyah (Academic Hospital Journal, 2025)
Background: In 2021, the International Diabetes Federation stated that there were around 536.6 million people suffering from DM worldwide, 90.2 million of whom were in Southeast Asia. Indonesia ranks 5th in terms of population with the highest DM in the world. The number of people with DM in Indonesia is around 19.5 million and is projected to increase to 28.6 million in 2045. The prevalence of Diabetes Mellitus in Yogyakarta is 2.4%. Diabetes Mellitus and TB are included in the top 10 diseases in Yogyakarta in 2023. Sleman is the second largest district after Bantul for the number of DM sufferers. Tuberculosis is a public health problem that is a global challenge and is the third highest cause of death in Indonesia and the first leading cause of death due to infectious diseases. TB management in Yogyakarta is not optimal when seen from Treatment Coverage and Treatment Success Rate data. Diabetes Mellitus is an important risk factor for the development of Active TB. TB screening in DM patients is necessary to prevent the development of active TB. This study aims to determine the percentage of TB patients from all DM patients treated at UGM Academic Hospital.Materials and methods: This research is descriptive quantitative research using primary and secondary data. Data analysis uses univariate analysis. The sample in this study was taken using a simple random sampling technique. There were 109 respondents who met the inclusion and exclusion criteria.Results: The results of the study showed that there was 1 (0.92%) DM patient who was positive for TB, 22 (20.18%) DM patients who were suspected of TB through the Perjaka 2M screening and 3 (2.75%) DM patients who were suspected of TB from thorax x-ray results.Conclusion: Screening is one of the efforts in finding TB cases that can be done actively or passively.